PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING PADA MATERI TEKS DRAMA DI SMP - Esterlina, Dwi; Rusminto, Nurlaksana Eko; Agustina, Eka Sofia (FKIP Universitas Lampung, 2020)
The problem in this research is how the development of a students’ worksheet based on discovery learning to drama text in junior high school and its’ eligibility as teaching materials. The purpose of the study is to describe the development of a students’ worksheet based on discovery learning to drama text in junior high school and its’ eligibility as teaching materials. This research uses research and development (rnd) method. The results of the study show that the form students’ worksheet based on discovery learning to drama text in junior high school that has been validated. Validation is conducted by expert lecturers to test the feasibility of the product. The result of the validator assessment of content aspect is on the percentage of 83.1% which belongs to very feasible category, meanwhile the assessment of practitioners on Indonesian language teachers on the learning aspects and the content aspects in percentage of 87.1% with very feasible category. Masalah dalam penelitian ini ialah bagaimanakah pengembangan lembar kerja peserta didik (LKPD) berbasis discovery learning pada materi teks drama di SMP dan kelayakannya sebagai bahan ajar. Tujuan penelitian ialah untuk mendeskripsikan pengembangan lembar kerja peserta didik (LKPD) berbasis discovery learning pada materi teks drama di SMP dan kelayakannya sebagai bahan ajar. Metode yang digunakan dalam penelitian ini ialah penelitian dan pengembangan (research and development/R D). Hasil penelitian menunjukkan bahwa produk lembar kerja peserta didik (LKPD) berbasis discovery learning pada materi teks drama di SMP yang sudah divalidasi. Hasil penilaian validator pada aspek isi dengan persentase 83.1% kategori sangat layak, sedangkan penilaian praktisi atau guru Bahasa Indonesia pada aspek pembelajaran dan aspek isi dengan sama-sama persentase 87.1% kategori sangat layak. Keywords: students’ worksheet development, discovery learning, drama text.